Security Frameworks: A Study on Different Approaches for the Internet of Things (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2016)
This paper provides an overview of some of the major works that focus on the use of security frameworks for Internet of Things environment to facilitate the development of applications for this scenario. The Internet of things or "IoT" is characterized by a high heterogeneity degree of devices and network protocols, where all kinds of communications appear to be possible, even unauthorized ones. As a result, requirements such as reliability, connectivity, privacy and security are becoming increasingly more critical. This paper discusses the applicability and limitations of the main existing security frameworks in the context of the Internet of Things.